2000
DOI: 10.1093/joc/50.4.133
|View full text |Cite
|
Sign up to set email alerts
|

Media bias in presidential elections: a meta-analysis

Abstract: A meta-analysis considered 59 quantitative studies containing data concerned with partisan media bias in presidential election campaigns since 1948. Types of bias considered were gatekeeping bias, which is the preference for selecting stories from one party or the other; coverage bias, which considers the relative amounts of coverage each party receives; and statement bias, which focuses on the favorability of coverage toward one party or the other. On the whole, no significant biases were found for the newspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 25 publications
3
121
0
3
Order By: Relevance
“…Here, Chuck Grassley is being critical of Romney's character and demeanor during the debate and accusing him of not being assertive enough. Altogether, there was a slight pro-Obama bias present in the on-screen Twitter feed, which reflects previous research that shows a slight pro-Democrat bias in network TV coverage of presidential elections (D'Alessio & Allen, 2000). Yet, in the same breath, it appears that there was no overwhelming partisan bias in the on-screen Twitter feed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Here, Chuck Grassley is being critical of Romney's character and demeanor during the debate and accusing him of not being assertive enough. Altogether, there was a slight pro-Obama bias present in the on-screen Twitter feed, which reflects previous research that shows a slight pro-Democrat bias in network TV coverage of presidential elections (D'Alessio & Allen, 2000). Yet, in the same breath, it appears that there was no overwhelming partisan bias in the on-screen Twitter feed.…”
Section: Discussionsupporting
confidence: 82%
“…At the same time, the mainstream media do not appear to show an overwhelming partisan bias during its presidential campaign coverage (D'Alessio & Allen, 2000), and there should be an effort to provide balanced coverage of the candidates on network TV (i.e., not cable news). Thus, we offer a research question about the neutrality of the on-screen visuals present during the presidential debates:…”
Section: Partisan Biasmentioning
confidence: 99%
“…And since the question of media bias has been most resonant in US debates about the political role of media, the Downloaded by [Istanbul Universitesi Kutuphane ve Dok] at 08:07 20 December 2014 300 H. Brandenburg design and methodology of this Irish case study largely takes its lead from similar studies in the US. McQuail (1992: 191) offers the following general definition of bias: 'a consistent tendency to depart from the straight path of objective truth by deviating either to left or right … In news and information it refers to a systematic tendency to favor (in outcome) one side or position over another '. D'Alessio and Allen (2000) not only give an overview of the literature on US media bias, which shows the increasing importance in political and academic debate, they also introduce a typology of forms of bias.…”
Section: Questioning the Political Role Of Irish Mediamentioning
confidence: 99%
“…Regarding the latter, much of the emphasis has been on resolving the issue of whether a liberal or conservative media bias exists (Entman, 2007;Groseclose & Milyo, 2005;D'Alessio & Allen, 2000), whereas the former has examined the psychological and demographic characteristics associated with perceptions of media bias. Here, research has shown that although many in the public believe the press to be biased (Baron, 2006) a number of different factors are found to correlate with perceptions of press bias, key amongst these is partisanship (Eveland & Shah, 2003).…”
Section: Introductionmentioning
confidence: 99%